Analisis Pengaruh Tingkat Kecemasan dan Konsistensi Belajar Terhadap Prestasi Belajar Matematika Siswa Kelas X SMA Islam Sinar Cendekia Kota Tangerang Selatan - Suyanto Suyanto (Departement of Mathematics Education, 2023)
One of the indicators of quality education, the measure is knowledge competency, namely learning achievement. The problems that students often face are anxiety in learning mathematics and students' consistency in learning, which affects their mathematics learning achievement. The purpose of this research is to determine (1) the partial influence of learning anxiety levels on mathematics learning achievement; (2) the partial influence of learning consistency on mathematics learning achievement; and (3) the influence of anxiety level and learning consistency simultaneously on mathematics learning achievement. This research was conducted with a quantitative approach using the correlation survey method. The sampling technique is random sampling. Data was collected using a questionnaire and the validity of the instrument was tested using Pearson Product Moment and the reliability of the instrument used the Cronbach Alpha formula. The data analysis technique for testing the first and second hypotheses is with a partial t test, then testing the third hypothesis with a simultaneous F test. The results of the research show that, (1) there is a positive and significant influence between the partial level of anxiety (X₁) on mathematics learning achievement (Y) as evidenced by the partial t-test showing the calculated t value (6.795) > t table (2.286); (2) there is a positive and significant influence between partial learning consistency (X₂) on mathematics learning achievement (Y) as evidenced by the partial t-test showing the calculated t value (3.786) > t table (2.286); (3) there is a positive and significant influence between anxiety level (X₁) and learning consistency (X₂) simultaneously on mathematics learning achievement (Y) as evidenced by the simultaneous F-test showing the calculated F value (49.814) > F table (3.115). The coefficient of determination is 0.537, which means that the contribution of the independent variables, level of anxiety and learning consistency, has an influence on the dependent variable of mathematics learning achievement of 53.7%. There are still 46.3% other factors that have not been researched which influence mathematics learning achievement.